Beyond Blame: What Investigations of Intelligence Failures Can Learn from Aviation Safety. Issue 3 (3rd July 2022) - Ingesson, Tony
Abstract: Investigations into intelligence failures are frequently conducted by multiple parties in parallel, and in several important cases, their conclusions have been controversial. In addition, investigations into minor incidents, such as mishandling of sensitive information or equipment, tradecraft errors, or similar events where no major consequences have been detected, tend to be handled internally by the concerned agency, or through limited interagency cooperation. This can lead to missed opportunities to prevent them from developing into major failures. These issues are compared to the investigative procedures employed in the aviation safety sector, where an independent body is responsible for investigating both major failures and minor incidents, with a view specifically to develop proactive measures to prevent repetition. The conclusion presented is that the Intelligence Community could benefit from studying how aviation safety investigations are handled, in order to be more effective in addressing minor incidents at an early stage, and to avoid controversies in investigations of major events.